2020
DOI: 10.1093/cvr/cvaa158
|View full text |Cite
|
Sign up to set email alerts
|

Dilated cardiomyopathy-linked heat shock protein family D member 1 mutations cause up-regulation of reactive oxygen species and autophagy through mitochondrial dysfunction

Abstract: Background During heart failure, the levels of circulatory HSPD1 (HSP60) increase. However, its underlying mechanism is still unknown. The apical domain of HSPD1 is conserved throughout evolution. We found a point mutation in HSPD1 in a familial dilated cardiomyopathy (DCM) patient. A similar point mutation in HSPD1 in the zebrafish mutant, nbl, led to loss of its regenerative capacity and development of pericardial edema under heat stress condition. In this study, we aimed to determine the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…HSPD1 acts as a significant regulator of cytokine production and interacts with interferon regulatory factor 3 (IRF3), which is a player in the NLR and IFN-ÎČ signaling pathway [ 46 , 47 , 48 ]. Enomoto et al reported that upregulation of HSPD1 protein inhibited the activity of mitochondrial complex IV, leading to an increase in ROS concentration in cardiac muscle [ 49 ]. Stefano et al found no difference in the expression of HSPD1 in NASH and control groups [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…HSPD1 acts as a significant regulator of cytokine production and interacts with interferon regulatory factor 3 (IRF3), which is a player in the NLR and IFN-ÎČ signaling pathway [ 46 , 47 , 48 ]. Enomoto et al reported that upregulation of HSPD1 protein inhibited the activity of mitochondrial complex IV, leading to an increase in ROS concentration in cardiac muscle [ 49 ]. Stefano et al found no difference in the expression of HSPD1 in NASH and control groups [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The HSPD1 gene encodes for a constitutively expressed Hsp60 chaperonin protein. A recent study has linked HSPD1 mutations with cardiomyopathy when the mutation p.Thr320Ala was described in a Japanese family with DCM and arrhythmia [ 69 ]. Although the mechanisms whereby HSPD1 may contribute to cardiomyopathy are unclear, the authors demonstrated that a similar mutation in zebrafish resulted in a DCM phenotype with mitochondrial damage and increased levels of reactive oxygen species, as well as a reduced tolerance to exercise stress [ 69 ].…”
Section: An Emerging Field: Heat Shock Protein and Molecular Chapementioning
confidence: 99%
“…A recent study has linked HSPD1 mutations with cardiomyopathy when the mutation p.Thr320Ala was described in a Japanese family with DCM and arrhythmia [ 69 ]. Although the mechanisms whereby HSPD1 may contribute to cardiomyopathy are unclear, the authors demonstrated that a similar mutation in zebrafish resulted in a DCM phenotype with mitochondrial damage and increased levels of reactive oxygen species, as well as a reduced tolerance to exercise stress [ 69 ]. Cardiac-specific deletion of the gene in mice resulted in the development of lethal DCM and HF in males, although the effects in females were not described [ 70 ].…”
Section: An Emerging Field: Heat Shock Protein and Molecular Chapementioning
confidence: 99%
“…To date, the role of autophagy has been unfolded in diverse paramount cardiac pathologies, including left ventricular hypertrophy [ 74 ], cardiomyopathies [ 75 , 76 ], and ischemic injury of the heart [ 77 ]. Despite extensive studies, however, the mechanisms responsible for the effects of autophagy on valvular diseases remain scarce, and no definitive results are available.…”
Section: Convergence Of Autophagy and Cavdmentioning
confidence: 99%